2023
DOI: 10.1200/jco.22.00642
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Update of Tisagenlecleucel in Pediatric and Young Adult Patients With Relapsed/Refractory Acute Lymphoblastic Leukemia in the ELIANA Trial

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. In the primary analysis of the global phase II ELIANA trial (ClinicalTrials.gov identifier:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 9 publications
1
86
0
Order By: Relevance
“…According to the ELIANA study, 71% and 59% of pediatric B-ALL patients developed BCA at 12 and 24 months, respectively. In this review, the most frequent grade 3/4 adverse event occurring >1 year after the infusion was infection, with a prevalence of 20.4% [7]. In adults, pathogen-specific antibodies can be detected in the blood due to CD19-negative plasma cells [60].…”
Section: B-cell Aplasia (Bca)mentioning
confidence: 94%
See 1 more Smart Citation
“…According to the ELIANA study, 71% and 59% of pediatric B-ALL patients developed BCA at 12 and 24 months, respectively. In this review, the most frequent grade 3/4 adverse event occurring >1 year after the infusion was infection, with a prevalence of 20.4% [7]. In adults, pathogen-specific antibodies can be detected in the blood due to CD19-negative plasma cells [60].…”
Section: B-cell Aplasia (Bca)mentioning
confidence: 94%
“…Tisagenlecleucel (tisa-cel), a second-generation CD19-directed chimeric antigen receptor (CAR) T-cell product, is an effective and well-tolerated therapy approved by the Food and Drug Administration for use in pediatric and young adult patients with R/R B-cell ALL and in adults with R/R/diffuse large Bcell lymphoma and R/R follicular lymphoma [5]. The pivotal ELIANA clinical trials [6] along with the recently published data [7] demonstrated high long-term (median follow-up of 38.8 months) relapsefree survival and OS rates of 52% and 63%, respectively, in children with B-cell ALL.…”
Section: Introductionmentioning
confidence: 99%
“…In the two articles that accompany this editorial, 2,3 we get both a longitudinal perspective on the use of CD19 chimeric antigen receptor (CAR) T-cells to achieve durable remissions in children and young adults with B-cell acute lymphoblastic leukemia along with insights for the role of combinatorial treatment approach with the infusion of two unique CAR T-cell products in optimizing remission rates. Collectively, these efforts strongly support the critically important role for CAR T-cells in children and young adults with B-cell acute lymphoblastic leukemia in achieving a cure—while laying a foundation for what future iterations of CAR T-cell–based approaches may look like to improve upon current outcomes.…”
mentioning
confidence: 99%
“…In a highly anticipated follow-up from the phase II study of tisagenlecleucel in childhood B-ALL, 4 Laetsch et al 2 expanded on their original analysis to report on long-term outcomes. With a total of 79 patients infused and a median follow-up of 38.8 months, the overall remission rate was 82% (n = 65) at 3 months—which excluded four patients with initial response at day 28 but had either interval therapy (n = 1), relapse (n = 2), or experienced nonrelapse mortality (n = 1) before 3 months.…”
mentioning
confidence: 99%
See 1 more Smart Citation